The Development of Sámi Sport, 1970–1990 : A Concern for Sweden or for Sápmi? - Lidström, Isak (The International Journal of the History of Sport, 2019)
It is widely agreed that sport and national identity are two interwoven phenomena. Recently, researchers have taken an interest in how sport has been used for nation-building purposes among groups not defined in terms of nation-states. These include the Sámi, an Indigenous people living in an area that extends over the northern parts of Norway, Sweden, Finland and Russia. Sámi championships and a Sámi national football team have been important elements in shaping a Sámi national identity across the state borders. Against this background, the historical development that led to the formation in 1990 of a Sámi National Sports Federation was highly complicated. The period from 1970 to 1990 was fraught by the dilemma of how sport was to be organized – based on the division of the Sámi by state borders or through a transnational Sámi sports organization. The outcome was a compromise in that the Sámi National Sports Federation was founded as an umbrella organization under which Sámi in Norway, Sámi in Finland, and Sámi in Sweden established separate and autonomous Sámi ‘district associations’.